Asymmetric Hydrogenation of Aryl Perfluoroalkyl Ketones Catalyzed by Rhodium(III) Monohydride Complexes Bearing Josiphos Ligands. Issue 46 (22nd July 2019) - Brüning, Fabian; Nagae, Haruki; Käch, Daniel; Mashima, Kazushi; Togni, Antonio
Abstract: The asymmetric hydrogenation of 2, 2, 2‐trifluoroacetophenones and aryl perfluoroalkyl ketones was developed using a unique, well‐defined chloride‐bridged dinuclear rhodium(III) complex bearing Josiphos‐type diphosphine ligands. These complexes were prepared from [RhCl(cod)]2, Josiphos ligands, and hydrochloric acid. As catalyst precursors, they allow for the efficient and enantioselective synthesis (up to 99 % ee ) of chiral secondary alcohols with perfluoroalkyl groups. This system does not require an activating base for the hydrogenation of 2, 2, 2‐trifluoroacetophenones. Additionally, the enantioselective C=O hydrogenations of 2‐phenyl‐3‐(haloacetyl)‐indoles, a class of privileged structures in medicinal chemistry, is reported for the first time. Abstract : Dinuclear Rh III monohydride complexes bearing Josiphos‐type ligands have been developed. These complexes serve as catalyst precursors for the efficient enantioselective carbonyl hydrogenation of trifluoroacetophenones. Related aryl perfluoroalkyl ketones and 3‐(haloacetyl)‐2‐arylindoles are viable substrates, affording the corresponding secondary alcohols in high yield and enantiomeric excess.